From Whitney to Chomsky : essays in the history of American linguistics - Joseph, John Earl (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences, 2002)
What is 'American' about American linguistics? Is Jakobson, who spent half his life in America, part of it? What became of Whitney's genuinely American conception of language as a democracy? And how did developments in 20th-century American linguistics relate to broader cultural trends?This book brings together 15 years of research by John E. Joseph, including his discovery of the meeting between Whitney and Saussure, his ground-breaking work on the origins of the 'Sapir-Whorf Hypothesis' and of American sociolinguistics, and his seminal examination of Bloomfield and Chomsky as readers of Saus.